Conceptions and pedagogical practices on the mathematical processes of teachers (2019)
The objective of this research work is to establish the disciplinary, didactic and pedagogical conceptions of teachers in the area of mathematics in basic education against the formative process by competences and mathematical processes. The relationship between the standards developed in the institution against those stipulated by the “Ministerio de Educación Nacional” of Colombia was analyzed. This research was developed considering a hermeneutical historical paradigm, guided by the integrated qualitative approach, from an ethnographic design and therefore microetnography as a method. The research contributes from the epistemological, pedagogical and didactic categories, towards the achievement of evidence related to the classroom practices of teachers where contextualized problematic situations do not prevail so that the classes of the students are routine, not very impactful and the environment or Space becomes unmanageable, they do not have an adequate use of educational texts, and the use of educational material such as technological tools is not evident.